Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I've come to the following ODE, and I'm not even sure where to start on finding the general solution: $$4\alpha\xi y''(\xi)+(\xi+2\alpha)y'(\xi)=0$$ Here, $\alpha$ is some positive constant. Can anyone help me out?

share|cite|improve this question
up vote 4 down vote accepted

$y'(\xi) = f(\xi)$. We have $$4 \alpha \xi f'(\xi) = (\xi + 2 \alpha) f(\xi) \implies \dfrac{f'(\xi)}{f(\xi)} = \dfrac{\xi + 2\alpha}{4 \alpha \xi} = \dfrac1{4 \alpha} + \dfrac1{2 \xi}$$ Can you finish it off from here by finding $f$ and hence $y$?

share|cite|improve this answer
    
Indeed I can! Thanks! – Cameron Buie Sep 25 '12 at 18:15

Generally, if we have $F(x,y',y'')=0$ (i.e. we don't have $y$ in our equation) then by putting $y'=u$ and so, $$y''=\frac{d}{dx}\bigg(\frac{dy}{dx}\bigg)=\frac{du}{dx}$$ the original equation $F(x,y',y'')=0$ will be the first order diff equation $F(x,u,\frac{du}{dx})=0$

share|cite|improve this answer
    
Much appreciated! – Cameron Buie Sep 25 '12 at 18:15

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.